Facilitation of pain sensitization in knee osteoarthritis and persistent post‐operative pain: A cross‐sectional study. (24th December 2013) - Skou, S.T.; Graven‐Nielsen, T.; Rasmussen, S.; Simonsen, O.H.; Laursen, M.B.; Arendt‐Nielsen, L.
Abstract Background Around 20% of patients with osteoarthritis (OA) have chronic post‐operative pain after total knee arthroplasty (TKA) and often undergo revision surgery with unfavourable pain outcome. This study compared sensitization in pain patients with knee OA and after revision TKA (re‐TKA). Methods Median pressure pain thresholds (PPTs) assessed from the most affected knee (localized sensitization) were used to subgroup 53 patients with OA pain and 20 patients with pain after re‐TKA: group 1: OA and high‐knee PPT; group 2: OA and low‐knee PPT; group 3: re‐TKA and high‐knee PPT; group 4: re‐TKA and low‐knee PPT. Clinical pain intensity was assessed using a visual analogue scale (VAS). Bilateral PPTs were measured from the lower leg and forearm (spreading sensitization). Furthermore, the pain intensities evoked by 10 repeated pressure pain stimuli (temporal summation) at the knee and lower leg were assessed on an electronic VAS. Results The mean clinical pain intensity was not significantly different between groups. The PPTs from both lower leg and forearm were significantly lower in group 4 compared to groups 1, 2, and 3 and in groups 2 and 3 compared to group 1 (p < 0.05). Temporal summations from the knee and lower leg were significantly facilitated in groups 3 and 4 compared to groups 1 and 2 (p < 0.05). Conclusions Despite similar pain intensities, facilitated temporal summation is worse in re‐TKA than in OA and patients with high local knee hyperalgesia show more prominent spreading sensitization. The study suggests that sensitization should be considered in knee OA especially before re‐TKA.